Transformative Pathways: Implementing Intercultural Competence Development in Higher Education Using Kotter's Change Model - Owura Kuffuor; Sakhi Aggrawal; Aparajita Jaiswal; Ronald J. Smith; Pamala V. Morris (MDPI AG, 2024)
This study explores the efficacy of Kotter's eight-step change model in fostering intercultural competence among faculty and staff within a large Midwestern public university. Recognizing the need for intercultural development in higher education, this research applies a structured change framework coupled with the Intercultural Development Inventory (IDI) assessment tool to guide the change process. The development of intercultural competence among faculty and staff is crucial for creating inclusive learning environments, as they play a pivotal role in modeling intercultural competence and fostering students' skills necessary to navigate an increasingly diverse and interconnected world. This study employs an instrumental case study design, utilizing interviews, document analysis, and Intercultural Development Inventory (IDI) assessments to examine the change process over a three-year period. The findings demonstrate how each step of Kotter's model was successfully adapted to drive organizational change and enhance intercultural competence among 639 faculty and staff members across 11 departments in the College of Agriculture. This study highlights the importance of creating a shared vision, empowering stakeholders, and anchoring changes in the institution's culture and emphasizes the pivotal role of structured change management in achieving substantive improvements in intercultural learning environments. The insights and strategies presented can serve as a foundation for other higher education institutions seeking to implement similar initiatives and foster inclusive learning environments.